Long-term outcomes in heritable thoracic aortic disease - Robertson, Elizabeth N.; Bannon, Paul G.; Jeremy, Richmond W. (Frontiers in Cardiovascular Medicine, 2022)
Heritable aortic aneurysm causes significant morbidity and mortality. Marfan syndrome is well-known, but clinical course and prognosis of other heritable aortopathies is less well defined, particularly for non-syndromal aortic disease. This study investigated presentation, clinical course and survival of patients with syndromal (Loeys-Dietz, Aneurysm-Osteoarthritis and Aneurysm-Cerebral Arteriopathy (ACTA2) syndrome) and non-syndromal heritable aortic disease in comparison to Marfan syndrome. The study group includes 536 individuals (283 Marfan, 176 non-syndromal heritable aortopathy, 36 Aneurysm-Osteoarthritis, 32 Loeys-Dietz and 9 ACTA2 aneurysm) enrolled in a longitudinal clinical follow-up between 1990 and 2022. Age at diagnosis differed between groups: Marfan = 22.0±16.6; Loeys-Dietz = 29.6±21.5; Aneurysm-Osteoarthritis = 36.4±18.8; ACTA2 aneurysm = 43.4±18.6; non-syndromal heritable aortopathy = 47.2±16.6 years (p<0.001). Aortic dissection was the presenting event in 8% individuals with Marfan compared to 27% with non-syndromal heritable aortopathy and 34% with Loeys-Dietz syndrome (p<0.01). Mean follow-up duration was 16.4 years (0.2 to 30 years) and 74 individuals died during follow-up (Marfan=52, Loeys-Dietz=6, Aneurysm-Osteoarthritis=4, ACTA2 aneurysm=1, heritable non-syndromal aortopathy=11). At 10 years follow-up, mean survivals were: Aneurysm-Osteoarthritis = 77.5±10.4%; Loeys-Dietz = 90.0±6.8%; Marfan = 94.6±1.4%; heritable non-syndromal aortopathy = 95.9±2.1% (NS). There were 60 aortic dissections (24 Type A, 36 Type B) during follow-up. At 10 years, survival free of dissection was comparable between groups: Aneurysm-Osteoarthritis = 90.7±6.4%; Loeys-Dietz = 94.4±5.4%; Marfan= 96.1±1.2%; heritable non-syndromal aortopathy = 93.9±2.3%, with similar findings at 20 years. Prophylactic aortic surgery was a first event during follow-up for 196 individuals (ACTA2 aneurysm=3; Aneurysm-Osteoarthritis=10; Loeys-Dietz=19; Marfan=119; heritable non-syndromal aortopathy=45). A second surgical intervention was required in 45 and a third intervention in 21 individuals. At 10 years follow-up, survival free of surgery was: Aneurysm-Osteoarthritis = 68.5±10.1%; Loeys-Dietz = 40.8±11.2%; Marfan = 75.5±2.7%; heritable non-syndromal aortopathy = 63.8±4.7% (p<0.001). At 20 years, survival free of surgery was: Aneurysm-Osteoarthritis = 26.6±14.7%; Loeys-Dietz = 9.1±8.2%; Marfan = 57.2±3.4%; heritable non-syndromal aortopathy = 41.6±8.2% (p<0.001). Diagnosis of non-syndromal heritable aortopathies is delayed compared to Marfan syndrome, with associated complications of aortic dissection. Survival of individuals enrolled in follow-up surveillance is comparable between aortopathies, however aortic dissections still occur and need for surgical intervention is high.